The Impact of Land and Building Tax on the Regional Economy (Regencies and Municipalities) in Indonesia using Panel Data Regression - Nur Farida Liyana; Heni Sulastri; Khusnaini; Ida Zuraida (Yayasan Ilomata, 2026)
Land and Building Tax (PBB-P2) is a major source of Regional Original Revenue (PAD) in the era of fiscal decentralization. As a tax imposed on the ownership or use of land and buildings, PBB-P2 has significant potential to support sustainable regional development financing. However, excessively high tax burdens or poor tax governance can discourage investors from investing in a region. This study aims to analyze the effect of PBB-P2 on the economic growth of districts/cities in Indonesia by including regional investment, the number of productive workers, and local government capital expenditure as additional explanatory variables. A quantitative approach was used using a panel data regression model, along with simultaneous and partial tests for each independent variable. The results show that simultaneously, PBB-P2, regional investment, productive workers, and government capital expenditure have a significant effect on regional economic growth. However, partially, only investment has a positive and significant effect on economic growth. PBB-P2 has a positive but insignificant effect, indicating that its role is more as a source of basic fiscal revenue than as a direct instrument for driving growth. This finding underscores the importance of improving human resource quality, capital expenditure effectiveness, and strengthening regional fiscal governance so that tax revenues, including PBB-P2, can be optimized as an instrument of inclusive and sustainable economic development. This research provides policy implications that increasing regional economic growth is not sufficient by simply increasing tax revenues, it also requires more productive and efficient investment, labor, and public spending management strategies.